Prevalence of HIV-1 pretreatment drug resistance among treatment naïve pregnant women in Bissau, Guinea Bissau - Wilhelmson, Sten (PLoS One, 2018)
BACKGROUND: With increased access to antiretroviral treatment (ART) in sub-Saharan Africa emergence of HIV-1 pretreatment drug resistance constitutes a serious risk. This may lead to rapid virological failure in subjects initiating ART, and mother-to-child transmission despite prophylaxis. METHODS: Treatment-naïve pregnant women from four antenatal care clinics in Bissau, Guinea-Bissau, were enrolled from October 2016 to November 2017. Genotypic resistance testing and phylogenetic subtype analysis was performed on 48 specimens. RESULTS: Forty eight women met the survey inclusion criteria. All specimens were successfully amplified and genotyped. Specimens from five women were associated with HIV-1 drug resistance mutations. Four carried mutations exclusively linked to non-nucleoside reverse transcriptase inhibitors (NNRTIs) (K103N, K103N/S) and one carried mutations to both NNRTIs (G190S, K101E) and nucleoside reverse transcriptase inhibitors (NRTIs) (M184V). These results corresponded to 10.4% (95% CI: 4.5–22.2%), 2.1% (95% CI: 0.4–10.9%) and 0% (95% CI: 0.0–7.4%) drug resistance mutations to NNRTIs, NRTIs and protease inhibitors, respectively. HIV-1 circulating recombinant form 02AG was most commonly found, followed by HIV-1 sub-subtype A3. Subtype/CRF was not associated with drug resistance mutations. CONCLUSION: Our study reports a 10.4% prevalence of pretreatment drug resistance to NNRTIs in HIV-1-infected pregnant women in the capital Bissau, Guinea Bissau. Since NNRTIs are part of first-line ART in the country, baseline resistance screenings or adjustment of national treatment guidelines should be considered as antiretroviral treatment programs are scaled up.